La contaminación fotoquímica en España. - Velázquez de Castro González, Federico (Observatorio Medioambiental, 2001)
The photochemichal pollution considered nowadays inside the main kind of atmospheric pollution at the developped countries. Ozone is the more important compound; it must be in the stratospheric levels beacause of its role against the shortest ultraviolet radiation, but it become a pollutant at the lowest atmospheric levels. Ots rate increasen about 1-2% per year beacause of the world, even in Spain Aceptado: 15/V/2001. * Doctor en Ciencias Químicas. 295 Federico Velázquez de Castro González La contaminación fotoquímica en España where the ozone levels are high, in special at climatic conditions. Therefore, it is necessary a fair environmental policy in order to prevent this new sort of pollution.
Keywords: Photochemichal pollution; developped countries; Spain